Fabrication, formation mechanism and the application in lithium-ion battery of porous Fe2O3 nanotubes via single-spinneret electrospinning. (10th March 2015) - Wang, Heng-guo; Zhou, Yuqi; Shen, Yu; Li, Yanhui; Zuo, Qinghui; Duan, Qian
Graphical abstract: Porous Fe2 O3 nanobelts and nanotubes have been controllably fabricated by annealing the different electrospun precursor nanofibers. When evaluated as a anode material for lithium-ion batteries, the porous Fe2 O3 nanotubes exhibit good lithium storage performances. Highlights: The one dimensional controllable Fe2 O3 nanostructures are prepared by electrospinning method. The mechanism for the formation of the controllable Fe2 O3 nanostructures is investigated. The electrospinning method is versatile, extensive, available and used extensively. The porous Fe2 O3 nanotubes exhibit good lithium storage performances. Abstract: Porous Fe2 O3 nanotubes have been fabricated by annealing the electrospun precursor nanofibers. Moreover, the mechanism for the formation of the controllable Fe2 O3 nanostructures is investigated through manipulating the concentration of the electrospun precursor solution and also discussed based on their morphological evolution processes. When evaluated as anode materials for lithium-ion batteries, the porous Fe2 O3 nanotubes exhibit good lithium storage performance with high specific capacity of 1407.9 mA h g −1 and good cycling stability (stable up to 250 cycles), which is attributed to the unique morphology of the porous, hollow and continuous one dimensional (1D) nanostructures. These results demonstrate that further improvement or optimization of electrochemical performance in metal oxide-based electrode materials could be realized by the design of 1D nanostructures with unique morphologies.